Role of Dermatoglyphics in Orthodontics - A. Hima Sai Chandana Devi; Anoosha Manda; C. V. Padma Priya; Praveen Kumar Varma Datla; Pradeep Kandikatla; N. Hari Babu; Rama Krishna Alla (Advanced Research in Biological Science Vol. 4, 2023)
Dermatoglyphics is an indispensable part of forensic odontology and has numerous applications in areas of science, such as anthropology, criminology, cytogenetic studies, and also in dentistry. Dermatoglyphics is a scientific study that deals with the epidermal ridges and their configurations on certain body parts such as fingers, palms, and soles. In humans, during the intrauterine life (IUL) the primary palate, lip, and dermal ridges are formed during the same period, the genetic code engineered in the genome normal or abnormal is mirrored on these developing structures.